2016
DOI: 10.5815/ijmecs.2016.05.01
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lecture Attendance on Exams for Novice Programming Students

Abstract: Abstract-In this paper, the correlation between lecture attendance and assessment tasks on final exam performance of introductory programming students has been analyzed to identify if lecture attendance, and completion of in-class and take home formative assessment tasks affects student performance in the final examination. In this study, only lecture attendance, homework exercises and class demonstration scores, and final exam marks have been considered. This study used Spearman's Rank correlation coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…However, students who complete the DE exercises are instructed to enter their solutions into ViLLE via the instructor's computer for subsequent marking. The marks for DEs are calculated by ViLLE on the basis of their registered responses in the lecturer's computer (Veerasamy et al, ). Both HE and DE are hurdles, and students should secure at least 50% in each category to be eligible to sit FE.…”
Section: Methodsmentioning
confidence: 99%
“…However, students who complete the DE exercises are instructed to enter their solutions into ViLLE via the instructor's computer for subsequent marking. The marks for DEs are calculated by ViLLE on the basis of their registered responses in the lecturer's computer (Veerasamy et al, ). Both HE and DE are hurdles, and students should secure at least 50% in each category to be eligible to sit FE.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, the study conducted by (Credé, et al, 2010) concluded that class attendance is a generally desirable behaviour, and there is encouraging evidence that mandatory policies are not necessary for dramatically improving class attendance or class performance. Another study conducted by (Veerasamy et al, 2016) concluded that attendance doesn't positively correlate with students' performance in the exams. Since attendance is compulsory at Indian University, further study needs to be conducted to understand why attendance proves to be ineffective towards student marks.…”
Section: Study Choicesmentioning
confidence: 99%
“…However, study shows that there are no concrete valuable predictor to predict the student performance as they are varied from one context to another context in variety of ways ,including cultural settings and students cohort. Several studies have been conducted on the impact of problem solving skill on student performance in various courses including the programming reported that students with problem solving skill may help academicians to identify and analyze student study habits and attitudes that are important to academic performance though it is theoretically unrelated to academic achievements (Veerasamy et al 2016)(Bubica and Boljat 2014). Similarly, the author reported there is a strong that there is a strong relationship between problem solving proficiency of sophomore mathematic students in a quantitative technology and their achievements in that course.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, the author reported there is a strong that there is a strong relationship between problem solving proficiency of sophomore mathematic students in a quantitative technology and their achievements in that course. In addition, several studies reported that gender differences does not have any impact on the learning outcome of the programming courses (Veerasamy et al 2016)(Bubica and Boljat 2014). Specifically our independent sample t tests results confirmed that there is no gender discrimination in related to their performance in introductory course by adopting the problem based leaning.…”
Section: Related Workmentioning
confidence: 99%